(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2023)
The present study aimed to evaluate the effect of the combination between nitrogen rates and the management of straw mulches for the cultivation of peppers. The treatments comprised three managements of straw on the ground (no straw, Urochloa ruziziensis, and millet) and five nitrogen rates (0, 50, 100, 150, and 200% of the recommended dose of 120 kg ha-1). Mulch presence results in better physiological activity in the plants, while the rates of N positively affect the physiological and biometric characteristics of the plants up to 127.50% and 181.21%, respectively. Rates up to 145.62% increased fruit length in the treatment composed of U. ruziziensis straw, while rates relative to 154.65%, 127.98%, and 138.55% for the control, U. ruziziensis and millet treatments provided productive gains of 202.52%, 267.44%, and 473.18%. We concluded that straw mulching improves the physiological condition of sweet pepper plants and the application of nitrogen fertilizer; using straw from millet plants, combined with the dose of 138.55% N, results in greater yield gains.